Factors Associated With The Empathetic of Staff at The Central Laboratory Installation of M. Djamil Hospital Padang - Annisa Safitri; Zelly Dia Rofinda; Nelmi Silvia (CV. Inara, 2026)
Empathy is a crucial component for healthcare professionals to build relationships with patients and improve the quality of care. However, it is often overlooked among laboratory personnel who tend to focus more on technical aspects. Individual and organizational factors are suspected to contribute to decreased empathy among laboratory staff. This study aimed to identify the factors associated with empathy among staff at the Central Laboratory Installation of M. Djamil Hospital Padang. This study employed a Mixed Method design using a Concurrent Embedded model involving 53 laboratory staff. Data were collected through questionnaires, in-depth interviews, observations, and document reviews. Quantitative data were analyzed using chi-square tests and logistic regression, with statistical significance set at p < 0.05. The results showed that the majority of respondents were aged 30–42 years (52.8%), female (77.4%), held a diploma degree (81.1%), had ≥5 years of work experience (84.9%), and had low empathy levels (56.6%). There were significant associations between age (p=0.043), education level (p=0.042), organizational support (p=0.005), workload (p=0.003), work stress (p=0.045), and work motivation (p=0.023) with empathy levels. Meanwhile, gender, length of service, and seminar/training attendance were not significantly associated with empathy. Multivariate analysis revealed that organizational support, workload, and work stress were the key factors associated with empathy, with organizational support emerging as the most dominant factor (p=0.004). Qualitative data supported these findings, indicating that high workload, lack of organizational support, and performance pressure were major barriers to demonstrating empathy toward patients. In conclusion, laboratory staff empathy is influenced by age, education, organizational support, workload, job stress, and work motivation, with organizational support being the most dominant factor.